Effect of pH and mixing ratios on the synergistic enhancement of Bambara groundnut-whey protein gels. (August 2021) - Diedericks, Claudine F.; Stolten, Vanessa; Jideani, Victoria A.; Venema, Paul; van der Linden, Erik
Abstract: Plant and animal-based protein mixtures are increasingly recognised as a new group of functional ingredients offering novel structuring capabilities. When combining new sources of plant and animal proteins, it is important to gain a mechanistic understanding of such mixtures to enable their use as food ingredients. In this study, we have investigated the synergistic enhancement of Bambara groundnut ( Vigna subterranea (L.) Verdc.) protein isolates [BGN-PI] when combined with whey protein isolates [WPI] in heat-induced gelled mixtures. Mixed proteins were characterised for their rheological and structural properties at 12% (w/w) total protein concentrations at three mixing ratios (70:30, 50:50 and 30:70) and three pH values (pH 3, 5 and 7), with comparison to the single protein systems. At acidic pH (pH 3) WPI dominated the gel formation of the mixed gels with BGN-PI having no effect, whilst close to the isoelectric point of both proteins at pH 5, BGN-PI lowered the gel strength of the mixtures. Synergistic enhancement was observed at pH 7, where independent of the BGN-PI concentration in the mixtures, the mixed gels were characterised with similar high gel strengths comparable to that of the single BGN-PI. Hence, BGN-PI dominated the elasticity of the mixed gel networks at neutral pH. Graphical abstract: Image 1 Highlights: Mixtures of Bambara groundnut protein isolates and whey protein isolates form gels upon heating. Synergistic enhancement of mixed gels evident at neutral pH. Bambara groundnut protein isolates dominate elasticity of mixed gels at neutral pH.